Solving Nonlinear Fractional Differential Equations for Contractive and Weakly Compatible Mappings in Neutrosophic Metric Spaces - Usman Ali; Haifa A. Alyousef; Umar Ishtiaq; Khaleel Ahmad; Shajib Ali (Journal of Function Spaces)
In this article, we aim to prove various unique fixed point results for contractive and weakly compatible mappings in the sense of neutrosophic metric spaces. Several nontrivial examples are also imparted. To support main result, uniqueness of solution of nonlinear fractional differential equations is examined.